Homoeopathic Approach to Osteomyelitis with its Pathological Significance (Advancements in Homeopathic Research, 2022)
The article on osteomyelitis encapsulates the advance  study in catastrophic manner. The disease covering  both stages of infection either its periprosthetic – joint  infection and osteonecrosis condition of the bone. The  innovative understanding with appropriate procedure  is given in detail for progressive or uncontrolled  condition of the patient. An inflammatory or serious  condition of the bone and its structure in later stages  caused by pyogenic infection. Myobacteria is rarely  causing primary epiphyseal osteomyelitis. Medullary  superficial or localized osteomyelitis developed on  the various affecting site of bone. Subsequent bone  damage is the end result of this ailment. The sequelae  of osteomyelitis vary, depending on age at onset, site  of infection, presence or absence of foreign bodies,  and presence or absence of adjoining joint infection. An impaired vascularity occurs in the infected  area that results in dead space/bone and repeated  occurrence of bone infection may travel into the  irreversible form causing the person restless, although  suffering from great despodency. Altered immune  defense mechanism may result in exaggerating the  disease due to various abnormal conditions as in  diabetic wound or from insufficient blood supply. A  proper intervention simultaneously with diagnosis  by corresponding symptomatology and investigation  is essential to understand the pathological process  along with the case progression. Homoeopathy can aid the process of recovery  in cases of osteomyelitis when the best selected  similimum along with miasmatic inference taken into  consideration.
Keywords: Chronic disease; Diathesis; Homoeopathy; Individualization; Miasm; Osteomyelitis